Determinats of Effective Tax Administrasion - A Case Study of Nambia - Eukeria WEALTH; Tapiwa Victor Warikandwa; William Claasen (University of Merdeka Malang, 2025)
Tax administration is an essential component of financial resource mobilization in developing countries. However, Namibia as a developing country has struggled to efficiently utilize tax administration as a mechanism for generating revenue and fostering economic development. This study thus investigates the determinants of effective tax administration, from a Namibian perspective. This study is premised on three variables; 1) organisational processes; 2) organisational resources; and 3) employee skills. Based on multiple regression analysis, the results of the study demonstrated a positive correlation between efficient tax administration and three variables namely organisational processes, organisational resources, and employee skills development. The variables were established as being central to enhancing effective tax administration. However, the Namibia Revenue Agency (NamRA), Namibia’s tax administration authority, was found wanting concerning all the variables. This has dire consequences for effective tax administration in the country a development which should be a cause for concern for policy makers and the tax authorities. The study is confined only to Namibia and to statistical methodologies pertinent to the discussion.